Critical limit of shade stress in lemongrass plant (Cymbopogon nardus L.) - Hartawan, Rudi; Nengsih, Yulistiati; Marwan, Edy; Adistya, Adilla; Nasamsir, Nasamsir; Nata, Dheno Bagas (Anjoro: International Journal of Agriculture and Business, 2025)
Lemongrass (Cymbopogon nardus L.) is well-known for its ability to thrive in sunlight. However, the capacity to tolerate shade when cultivated as an intercrop is unknown. Therefore, this study aimed to determine the tolerance limit of shade to the growth and production of lemongrass oil. A completely randomized design was used, with the treatment design varying by level of shade: control (without shade), 25%, 50%, and 75% shade. The parameters observed were light intensity, plant height, number of tillers, fresh weight of herbs, leaf thickness, leaf chlorophyll, and essential oil content. The results showed that 75% shade reduced light intensity by 75.38%, the number of tillers by 50.86%, fresh weight by 22.39%, leaf thickness by 31.91%, leaf chlorophyll by 54.96%, and essential oil content by 48%. The relationship pattern between shade and fresh weight of herbs was Y = -0.00733X2 + 0.3633X + 340.44, with a correlation of 0.70 and a determinant of 83.70%. Meanwhile, the relationship pattern between shade and leaf chlorophyll content was Y = -0,00029X2 +0.0093 + 47.26, with a correlation of 0.9681 and a determinant of 98.3%. In conclusion, lemongrass planted as an intercrop can tolerate 25% shade, as evidenced by its growth indicators and essential oil production.